The effects of naphthaleneacetic acid and gibberellic acid in prolonging bract longevity and delaying discoloration of bougainvillea spectabilis - Saifuddin, Mohammed; Hossain, A.B.M.S.; Osman, Normaniza; Boyce, Amru Nasrulhaq; Moneruzzaman, K.M. (Asian Network for Scientific Information, 2009)
In this study, experiments were conducted to investigate the effects of NAA and GA3 on bract longevity under exposed sunlight conditions and six months of observation. Bougainvillea bracts at four different stages of bract development were sprayed with gibberellic acid (100 ppm GA3), naphthaleneacetic acid (50, 100 and 150 ppm NAA) and mixed GA3 (100 ppm) and NAA concentrations (50,100 and 150 ppm). Bract longevity was found to be almost 10 days longer in NAA (50, 100 and 150 ppm) than in the water control and in GA3 (100 ppm) treatment. In the case of GA3 and NAA (50, 100 and 150 ppm) treatment on alternative days, bract longevity was 30 days longer when compared with the water control. It was also observed that a delay in discoloration and stomata conductance were increased in the presence of GA3 with low a concentration of NAA. The results indicated that the prolonging effect of low concentrations of NAA at the initial budding stages was more effective compared with its application at other stages of development and at higher concentrations. Maximum bract weight and shoot length were observed in the GA3 and GA3 plus NAA treated flowers.